Non-food uses of sharks in southern Bahia, Brazil - Barbosa-Filho, Márcio Luiz Vargas; Siciliano, Salvatore; Ann Hauser-Davis, Rachel; Barros Gonçalves de Souza, Gabriel; Romeu Nóbrega Alves, Rômulo; Medeiros Costa Neto, Eraldo (Ethnobiology and Conservation, 2024)
Sharks are a highly threatened group, and the threats these animals face also affect the cultural ways artisanal fisher communities interact with them. Consequently, local knowledge arising from human interactions with these animals also becomes threatened, as well as the potential of fisheries management through ethnoconservation. In this sense, this study examines the dynamics of shark use by fishers in northeastern Brazil. In 2012, data was collected through semi-structured interviews about shark uses applied to 65 traditional fishers who use sharks differently. The ways fishers use these fish are changing mainly because fishers informed an overall reduction in shark catches. Thus, the analysis of their uses comprises a historical-anthropological record, as specific interactions are quickly disappearing. Therefore, the variety of utilitarian connections and changes in shark use patterns over time reveal both ecologic and cultural extinction threats of the traditional shark fisheries in this area. We suggest implementing anthropological and biological studies that aim to contribute to the maintenance of the livelihoods of populations that interact with sharks and seek to guarantee the sustainable exploitation of these animals.